Come as You Are: Examining Autistic Identity Development and the Neurodiversity Movement through an Intersectional Lens - Botha, Monique; Gillespie-Lynch, Kristen (Human development, 2022)
Abstract Singer intended for neurodiversity to be a new category of intersectionality. However, intersectionality has been neglected in autism research and practice. This paper aims to inform an intersectional approach to autism by exploring autistic identity development in relation to other marginalized identities. We reviewed literature about neurodiversity, intersectionality, discrimination, and the identity development of autistic people, racial/ethnic minorities, and gender and sexual minorities. We discuss minority stress and evidence that cultural traditions alleviate it. Autistic culture can reframe personal difficulties as a politicized struggle. While the stereotype of autism is one of withdrawal, the history of autistic people coming together for justice defies this notion. Intersectionality teaches us that we must understand differences within the autistic community if we wish to help all autistic people experience the dignity they deserve. Using an intersectional lens, we can become more flexible in our understanding of positive autistic identity development and strategies to promote it.